Hybridization promotes speciation in Coenonympha butterflies. Issue 24 (December 2015) - Capblancq, Thibaut; Després, Laurence; Rioux, Delphine; Mavárez, Jesús
Abstract: Hybridization has become a central element in theories of animal evolution during the last decade. New methods in population genomics and statistical model testing now allow the disentangling of the complexity that hybridization brings into key evolutionary processes such as local adaptation, colonization of new environments, species diversification and extinction. We evaluated the consequences of hybridization in a complex of three alpine butterflies in the genus Coenonympha, by combining morphological, genetic and ecological analyses. A series of approximate Bayesian computation procedures based on a large SNP data set strongly suggest that the Darwin's Heath ( Coenonympha darwiniana ) originated through hybridization between the Pearly Heath ( Coenonympha arcania ) and the Alpine Heath ( Coenonympha gardetta ) with different parental contributions. As a result of hybridization, the Darwin's Heath presents an intermediate morphology between the parental species, while its climatic niche seems more similar to the Alpine Heath. Our results also reveal a substantial genetic and morphologic differentiation between the two geographically disjoint Darwin's Heath lineages leading us to propose the splitting of this taxon into two different species.